2018
DOI: 10.1016/j.jri.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Elevated systemic microbial translocation in pregnant HIV-infected women compared to HIV-uninfected women, and its inverse correlations with plasma progesterone levels

Abstract: In HIV infection, increased adverse perinatal outcomes reported among HIV-associated pregnancies are not fully understood. Currently, microbial product translocation (MT) from a permeable mucosa is demonstrated as a driver of inflammation, and may contribute to preterm delivery in HIV. Here, our results showed that plasma LPS levels (a representative marker of MT) were increased in HIV-infected women in the first and second trimester. Progesterone levels were significantly decreased in HIV-infected subjects in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 10 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…For example, intestinal damage resulting from low level ischemia or inflammation may share common pathways with placental insufficiency. 38 Increased microbial translocation has also been associated with reduced progesterone levels among pregnant PWLHIV, 39 which has been associated with preterm birth and may be associated with stillbirth. 40 Additional studies are needed to confirm our findings and to elucidate the potential mechanisms linking these maternal EED biomarkers to the risk of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…For example, intestinal damage resulting from low level ischemia or inflammation may share common pathways with placental insufficiency. 38 Increased microbial translocation has also been associated with reduced progesterone levels among pregnant PWLHIV, 39 which has been associated with preterm birth and may be associated with stillbirth. 40 Additional studies are needed to confirm our findings and to elucidate the potential mechanisms linking these maternal EED biomarkers to the risk of stillbirth.…”
Section: Discussionmentioning
confidence: 99%
“…54 Plasma progesterone levels during human pregnancy are inversely correlated with plasma lipopolysaccharide, a marker of microbial translocation. 57 , 59 Taken together, this evidence suggests that the ovarian hormones estradiol and progesterone are important in limiting intestinal permeability and preventing microbial translocation.…”
Section: Menopause and Microbial Translocationmentioning
confidence: 91%
“…This study further suggests that intestinal MT may be an important factor in the preterm delivery of HIV-infected pregnant women. Zhou et al 66 found that plasma LPS level increased in preterm pregnant women infected with HIV, and progesterone level significantly decreased in subjects infected with HIV in early pregnancy and middle pregnancy. It indicated a significant negative correlation between plasma LPS and progesterone.…”
Section: Gut Microbiome In Human Immunodeficiency Virus (Hiv) Infecti...mentioning
confidence: 99%